THE EFFECT OF JOB SATISFACTION ON THE SUCCESS OF SPORTS EVENTS OF ASSOCIATIONS IN MISAN GOVERNORATE - Ali Abbas Hasan; Munadhil Adil Kasim (Proximus Journal Publishing, 2025)
This research investigated the influence of work satisfaction on organisational success. The research was performed within sports federations, specifically involving four disciplines: football, basketball, volleyball, and handball. The study was conducted on a random sample of 47 employees across various administrative levels. The study employed a questionnaire as the primary instrument for data collection, supplemented by personal interviews and observations. The study aimed to evaluate several primary and secondary hypotheses concerning the influence among the study variables, to address the research questions and achieve the established objectives. To process data and information, many statistical approaches were employed, including mean, standard deviation, percentages, and simple regression coefficient. The study concluded that the two primary variables in the examined Association s were at elevated levels, that substantial relationships existed between them, and that work satisfaction had a considerable impact on organisational success. The results were congruent with the study's hypotheses. Recommendations were formulated based on the study's findings. The primary concern was the necessity for the federations' departments to educate employees about the significance of job satisfaction, as well as the imperative for senior management in sports federations to prioritise the organisation of training programs for leaders and managers, aimed at enhancing their understanding of job satisfaction and contemporary administrative strategies that facilitate its attainment and enhancement. In addition to promoting, reinforcing, and integrating this into its diverse policies and programs concerning human resources, there is a must to educate managers on these abilities and attributes. Furthermore, sports federations must establish standards and indicators in their operations and interactions with the public and society at large to ensure success through various means and techniques.
Keywords: Job Satisfaction; Success; Sports Events; Associations